Creating and Deploying USB Port Covers at Hudson County Community College. - Sanchez, Lotta; DeLooper, John (Information Technology & Libraries, 2019)
In 2016, Hudson County (NJ) Community College (HCCC) deployed several wireless keyboards and mice with its iMac computers. Shortly after deployment, library staff found that each device's required USB receiver (a.k.a. dongle) would disappear frequently. As a result, HCCC library staff developed and deployed 3D printed port covers to enclose these dongles. This, for a time, proved very successful in preventing the issue. This article will discuss the development of these port covers, their deployment, and what worked and did not work about the project.